Steel components for packaging devices in sliding/rolling contact: Metallurgical failure analysis. (August 2019) - Bertuccioli, C.; Ceschini, L.; Martini, C.
Abstract: This paper presents a case study in sliding/rolling contacts between steel components operating in packaging devices for powder pressing, where the non-conformal contact involving a rotating roller (AISI M2 tool steel) and pins (AISI 440B martensitic stainless steel) led to the formation of macro- and micro-pitting on both mating surfaces. On the basis of metallurgical failure analysis, surface-origin contact fatigue was identified as the main damage mechanism. Microstructural stress raisers such as relatively large carbides, clustered along plastic flow lines, were observed in both steels. A white etching layer (WEL), due to severe sliding/rolling conditions, further enhanced the formation of surface-origin cracks on the roller. Graphical abstract: Unlabelled Image Highlights: Failure analysis of steel roller and pins after field operation. Morphological and microstructural evaluation of the damaged surfaces. Surface-origin cracks due to contact fatigue as main cause of damage. Identification of microstructural stress raisers influencing the contact fatigue behavior.